The Hungarian Urban Network at the End of the Second Millennium - Beluszky, Pál (Discussion Papers, 1999)
The formation and evolution of the Hungarian urban network show characteristics which are different from the Western European urbanisation. These characteristics features do not only originate from the “belatedness”, but can also be attributed to the location of Hungary compared to the historical regions of Europe (Hungary is a Central European country, and this definition does not only have a geographical relevance), the repeated change of this comparative location and the fact that the “organic” urban development had been interrupted by forced pauses which lasted for several decades or centuries: the conquest of the Ottoman Empire in the 16th and 17th century, in the 20th century our forced position in the “eastern block” for more than four decades. In both periods, the features characteristic of the Eastern European (in fact, Asian) development path strengthened in Hungary. The aim of this study is to describe the urban development in Hungary, as well as the “condition” of the Hungarian urban network prior to the EU accession.